2004
DOI: 10.1002/path.1608
|View full text |Cite
|
Sign up to set email alerts
|

Localization of degradative enzymes and their inhibitors in the degenerate human intervertebral disc

Abstract: The histological and biochemical changes that occur in the extracellular matrix of the intervertebral disc (IVD) during ageing and degeneration have been investigated extensively. However, the mechanisms behind these changes are not fully understood. A number of studies have suggested the involvement of matrix metalloproteinases (MMPs) and ADAMTS in IVD degeneration, but few have localized the site of production of these enzymes to the cells of the degenerate disc. This study uses immunohistochemical technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
384
1
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(419 citation statements)
references
References 52 publications
25
384
1
9
Order By: Relevance
“…Numerous studies in literature have examined the protein expression levels of MMPs and ADAMTS in human herniated discs [10,19,20,26,29]. Using immunohistochemical techniques, Weiler et al [29] found a significant correlation between MMP protein activity and histological signs of degeneration in human IDs.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies in literature have examined the protein expression levels of MMPs and ADAMTS in human herniated discs [10,19,20,26,29]. Using immunohistochemical techniques, Weiler et al [29] found a significant correlation between MMP protein activity and histological signs of degeneration in human IDs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as matrix equilibrium shifts to a pro-catabolic state with advancing degeneration in articular cartilage, collagenasemediated degradation of type II collagen becomes more prominent (Hollander et al, 1994;Billinghurst et al, 1997). Among the collagenases, collagenase-3 (MMP-13) has been found to play a significant role in the development of both OA and DDD (Billinghurst et al, 1997;Fernandes et al, 1998;Anderson et al, 2002;Le Maitre et al, 2004). In articular cartilage, MMP-13 is almost exclusively produced by chondrocytes and has a dual role in ECM *Correspondence to : Hee-Jeong Im, Ph.D., Cohn Research BD 516, 1735 W. Harrison, Chicago, IL 60612, 312-942-3091 (Tel), 312-942-3053 (fax), Email : Hee-Jeong_Sampen@rush.edu.destruction as it degrades bothaggrecan and collagen type II (Fosang et al, 1996;Mitchell et al, 1996;Reboul et al, 1996;Fernandes et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In articular cartilage, MMP-13 is almost exclusively produced by chondrocytes and has a dual role in ECM *Correspondence to : Hee-Jeong Im, Ph.D., Cohn Research BD 516, 1735 W. Harrison, Chicago, IL 60612, 312-942-3091 (Tel), 312-942-3053 (fax), Email : Hee-Jeong_Sampen@rush.edu.destruction as it degrades bothaggrecan and collagen type II (Fosang et al, 1996;Mitchell et al, 1996;Reboul et al, 1996;Fernandes et al, 1998). In the IVD, MMP-13 expression increases with increasing severity of disc degeneration (Le Maitre et al, 2004). Therefore, defining the key factors, receptors, and regulators of MMP-13 expression is important to clearly understand the molecular etiology of OA and DDD.…”
Section: Introductionmentioning
confidence: 99%
“…Certain markers of altered cell metabolism, such as increased cytokine and MMP activity, 100,101 could be used as a definition. They are associated with structural defects in the disc, 27 but currently available markers are unable to differentiate degeneration from growth, adap-tive remodeling, and healing.…”
Section: Interpretation: What Is Disc Degeneration?mentioning
confidence: 99%